Mutagenicity Factor Determination of Mutant (HPRT1) Gene for V79 in Consequence of Exposure to Low Energy Levels of Alpha Particles - الغول, بوبكر علي يوسف (The Libyan Journal of Science, 2020)
The exposure from ionizing radiation may be represented by production of many unsystematic biological lesions which is well established recently. One approach which must be followed is quantifying the lesions occurring in living cells. One needs to specify the response properties of the irradiated biological material as well as the specifications of ionizing radiation quality for charged particles. In this research, the mathematical interpolation techniques were applied to determine the missing values of physical parameters. As the biological cells parameters, were determined based on the dose-response relationships published in the literature for mutations that occurred in HPRT1 gene for V79 Chinese hamster cells lines. These cells were exposed in vitro for low energy levels alpha particles. The finding of this research is that the mean the free path for linear primary ionization represents the best physical parameter in determining the mutagenicity for alpha particles. The mutagenicity factor determined based on this parameter, for low energy levels alpha particles, was 98%.